Proceedings of the Internet Measurement Conference 2018 2018
DOI: 10.1145/3278532.3278553
|View full text |Cite
|
Sign up to set email alerts
|

Who Knocks at the IPv6 Door?

Abstract: DNS backscatter detects internet-wide activity by looking for common reverse DNS lookups at authoritative DNS servers that are high in the DNS hierarchy. Both DNS backscatter and monitoring unused address space (darknets or network telescopes) can detect scanning in IPv4, but with IPv6's vastly larger address space, darknets become much less effective. This paper shows how to adapt DNS backscatter to IPv6. IPv6 requires new classification rules, but these reveal large network services, from cloud providers and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Despite their large vantage point into IPv6 scanning behavior, their study also only identified trace amounts of IPv6 scanning. More recently, in 2018, Fukuda and Heidemann [36] proposed using DNS backscatter to identify IPv6 scanning activity. Of note is the fact that this was the first study to find evidence of widespread IPv6 scanning activity.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite their large vantage point into IPv6 scanning behavior, their study also only identified trace amounts of IPv6 scanning. More recently, in 2018, Fukuda and Heidemann [36] proposed using DNS backscatter to identify IPv6 scanning activity. Of note is the fact that this was the first study to find evidence of widespread IPv6 scanning activity.…”
Section: Related Workmentioning
confidence: 99%
“…Previous work with similar goals performed observational studies using passive measurements of unsolicited traffic. While observational studies provide useful insights they (1) do not identify address discovery strategies leveraged by scanners and (2) may not be representative of the real scanning activity observed by actively in-use IPv6 networks [26,34,36,46] ( §2). In contrast, we take an active approach by conducting controlled experiments to evaluate the impact of IPv6 host activity on scanner behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we use a similar threshold to previous work in IPv4 [22]. We point out that other works have used less strict definitions of a scan, e.g., requiring a source to target fewer addresses, such as 25 [5] or only 5 [12]. We acknowledge that our strict large-scale definition may miss smallscale scans, but at the same time greatly reduces the number of CDN connection artifacts that we otherwise may mis-classify as scanning activity.…”
Section: Scan Detectionmentioning
confidence: 99%
“…There are also a few works focused on the detection and defense of IPv6 scanning. Fukuda et al [56] introduce an approach to detect IPv6 scanning and evaluate relevant severity. Plonka et al [57] introduce kIP, a new approach to increase the anonymity of IPv6 addresses.…”
Section: Ipv6 Address Space Securitymentioning
confidence: 99%